Advanced Algorithm for Optimizing the Deployment Cost of Passive Optical Networks - Pavel Lafata (Advances in Electrical and Electronic Engineering, 2013)
The deployment of passive optical networks (PONs) is slow today, especially in Europe, because completely new optical infrastructures are necessary to be installed in the last-mile segments of access networks, which is always very expensive process. One of the possibilities is to design economically effective topologies and to optimize the deployment cost. This article describes the method leading to evaluate an algorithm for designing suboptimal economic solutions and topologies for PONs by focusing on optimization of constructional length of distribution networks. While the typical PON topologies are star topologies or tree-star topologies, the first part of this article introduces new sub algorithm for estimating the minimum star topology. The next section brings the evaluation of two sub algorithms for solving minimum constructional length problems. Finally, all these parts will be merged into a complex algorithm by using clusterization technique to solve optimum topologies. However, the current version of presented algorithm is purely based on mathematical theories and was implemented in Matlab environment. Therefore, it is able to design only theoretical optimum topologies without taking external conditions and real limitations into account. These real conditions will be further implemented in the future, so the algorithm could be also used for practical applications.